Students’ Anxiety in Learning English (A Study at the 8th Grade of SMPN 6 Mataram) - Baiq Novianti Agustina; Nurachman Hanafi; Lalu Nurtaat; I Made Sujana (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
Anxiety has been expected to came failure in learning English. This study aimed to identify the levels of anxiety experienced by the students in learning English and what factors students believed contributed to their anxiety in learning English at the 8th grade of SMPN 6 Mataram. The method used in this study was qualitative, and the population consisted of 352 students, and 30 students (10%). were selected as the sample. Data collection techniques included questionnaires from Horwitz & Cope (1986) and in-depth interviews from Price (1999). The results shows that no students were indicated as being very anxious and anxious levels, 14 participants (47%) were mildly anxious, 13 participants (43%) were at the relaxed level, and 3 participants (10%) were very relaxed. Students experienced class anxiety, which affected them negatively. Therefore, it was essential for English teachers to be aware of the anxiety among their students. It is also found that seven factors were found in this research, coming from both teachers and students. The anxiety factors from the teachers were teacher personality 3 participants (10%), speaking in front of the class 12 participants (40%) and incomprehensible input 7 participants (23%). While factors from students were student beliefs about English being difficult 22 participants (73%), ridiculed by peers 9 participants (30%), lack of preparation 12 participants (40%) and low self esteem 8 participants (27%). Apart from that, these factors were discussed in this study, deepening our understanding of foreign language anxiety.